Quality of life in moderate to severe obstructive sleep apnea individuals before and after continuous positive airway pressure treatment - Alves, Paulo Roberto Ramos (2016)
Introduction: Obstructive sleep apnea (OSA) is characterized by recurrent episodes of partial or total obstruction of the upper airway, lasting at least ten seconds each in a frequency greater than five episodes per hour during sleep. Objective: To analyze the quality of life of individuals with OSA after treatment with continuous positive airway pressure (CPAP). Methods: Twenty individuals with OSA and apnea-hypopnea index (AHI) greater than 15, identified by polysomnography (PSG), were submitted to two quality of life questionnaires before and after CPAP treatment. Results: Twenty subjects completed the protocol. Mean age was 57±10 years, mean body mass index (BMI) was 31.6±4.5 kg/m2 and neck circumference (NC) average was 38.7±2.8 cm. We noted an average loss of 6.6±4.6 points in the Epworth scale and 6.6±1.5 points on the Stanford scale, besides gains ranging from 5 to 100 points on the scale of quality of life. Conclusion: CPAP improves quality of life in moderate to severe OSA individuals.